Reconstructing Islamic Education Through The Qur'anic Ecological Paradigm: Thematic Analysis of Surah Ar-Rum 41 and Surah Al-An‘Am 141 in Responding to The Contemporary Environmental Crisis - Syamsudin, Syamsudin; Muslihan, Muslihan; Rasyidi, Abdul Haris (Jurnal Ilmiah Profesi Pendidikan, 2026)
The increasingly severe environmental degradation indicates not only an ecological crisis but also a crisis of humanitarian awareness and weak internalization of ethical and spiritual values. This study aims to analyze the ecological values contained in the Qur’an, specifically Surah Ar-Rum verse 41 and Surah Al-An‘am verse 141, and to examine their relevance to Islamic education and public environmental policy. The research employs a qualitative approach using a field study method combined with descriptive analysis and thematic interpretation (tafsir maudhu‘i). Empirical data were collected through observations and in-depth interviews with educators, religious leaders, and public policy makers. The findings reveal that Qur’an-based ecological Islamic education has strategic potential as a medium for transforming values that integrate theological, pedagogical, and environmental policy dimensions. It can foster a transformative, humanistic, and ecologically responsive paradigm of Islamic education while supporting the development of public policies grounded in Islamic ethical principles. In conclusion, the internalization of Qur’anic ecological values through Islamic education can contribute significantly to addressing the ecological crisis and strengthening value-based environmental governance.